2018
DOI: 10.31557/apjcp.2018.19.12.3467
|View full text |Cite
|
Sign up to set email alerts
|

Probably Benign Solid Breast Lesions on Ultrasound: Need for Biopsy Reassessed

Abstract: Objective: To determine the negative predictive value of ultrasound for breast masses with probably benign morphology, and to assess whether follow-up may be an acceptable alternative to biopsy. Methods: After Institutional Review Board approval, all solid breast masses categorized as probably benign (American College of Radiology Breast Imaging Reporting and Data System [BI-RADS] 3) on ultrasound from January 2014 to December 2015, and having either tissue diagnosis or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Mammography is the gold standard for breast cancer detection; whereas, some studies have shown that breast ultrasonography is increasingly important in the qualitative diagnosis of solid masses with a higher diagnostic value, in which two-dimensional ultrasonography plays a crucial role in the clinical diagnosis of malignant masses, which can clearly show the morphological characteristics [13][14][15][16]. In this study, the ultrasonogram of benign and malignant masses was significantly different regarding size, shape, margin, internal echo, microcalcification, lateral acoustic shadow and posterior acoustic enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…Mammography is the gold standard for breast cancer detection; whereas, some studies have shown that breast ultrasonography is increasingly important in the qualitative diagnosis of solid masses with a higher diagnostic value, in which two-dimensional ultrasonography plays a crucial role in the clinical diagnosis of malignant masses, which can clearly show the morphological characteristics [13][14][15][16]. In this study, the ultrasonogram of benign and malignant masses was significantly different regarding size, shape, margin, internal echo, microcalcification, lateral acoustic shadow and posterior acoustic enhancement.…”
Section: Discussionmentioning
confidence: 99%